2H‐Naphthopyran‐Based Three‐State Systems: From Solution Studies to Photoresponsive Organic/Inorganic Hybrid Materials. Issue 11 (9th August 2018) - Vlajić, Marina; Schmidt, Johannes; Thomas, Arne; Rück‐Braun, Karola
Abstract: Densely packed self‐assembled monolayers with photoresponsive naphthopyrans attached to COOH headgroups on Si(111) were studied at the solid/inert‐gas interface. We demonstrate that 2 H ‐naphtho[1, 2‐b]pyrans are suitable three‐state photochromic systems for solution and surface studies. Switching between three states on the surface was realized using UV light, thermal relaxation and visible light as trigger and release elements as analyzed by ATR‐FTIR. Compared to solution studies, surface polarity and environmental effects, especially steric hindrance, contribute to state formation by stabilization of photoisomers, acceleration and deceleration of photochemical processes, and slowed down of thermal fading. Abstract : At the flick of a switch : State formation during switching of naphthopyrans attached to COOH headgroups on Si(111) is influenced by surface polarity and steric hindrance, leading to acceleration and deceleration of photochemical processes, as well as slower thermal fading. These environmental effects allow switching between three states by UV light, thermal relaxation and visible light, with readout by IR spectroscopy.